THE EFFECT OF PICTURE SERIES ON THE THIRD YEAR STUDENTS’ ABILITY IN WRITING NARRATIVE TEXT AT MTS MUHAMMADIYAH 02 PEKANBARU - Dilloka, Lengria Phahesya; Marzuki, Marzuki; Afrianto, Afrianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is aimed at finding out whether or not there is a significant effect of using picture series as media in teaching writing of the third year students of MTS Muhammadiyah 02 Pekanbaru in the Academic Year 2018/2019 in writing narrative text. The research design is experimental research with one group pre-test– treatment – post-test design. The sample of the research was 30 students IX 5 chosen by using cluster random sampling technique. The data were collected by giving a writing test about a narrative text (pre-test and post-test) to the students. The data were analyzed by using t-test formula. The results of data analysis showed that the mean score of the posttest was higher than the mean score of the pretest (62.73 > 50.22). The value of the t-test was 7.65 while the value of the t-table in significance level of 5% df=23 is 2.069. Since the value of the t-test was higher than t-table, it can be concluded that Alternative hypothesis (Ha) was accepted and the Null Hypothesis (Ho) was rejected. It means that there was a significant effect of using picture series as media in teaching writing to the third year students of MTS Muhammadiyah 02 Pekanbaru. It is suggested that Picture Series is appropriate to be applied in teaching to improve students’ writing ability, especially in writing narrative texts as media.Key Words: Picture Series, Writing ability, Narrative Text